Saponins, IL12 and BCG adjuvant in the FML-vaccine formulation against murine visceral leishmaniasis - Santos, W. R.; de Lima, VMF; de Souza, E. P.; Bernardo, R. R.; Palatnik, M.; de Sousa, CBP (Elsevier B.V., 2002)
The FML antigen of Leishmania donovani, in combination with either Riedel de Haen (R), QuilA, QS21 saponins, IL12 or BCG, was used in vaccination of an outbred murine model against visceral leishmaniasis (VL). Significant and specific increases in anti-FML IgG and IgM responses were detected for all adjuvants, and in anti-FML IgG1, IgG2a and IgG2b and delayed type of hypersensitivity to L. donovani lysate (DTH), only for all saponins and IL12. The QS21-FML and QuilA-FML groups achieved the highest IgG2a response. QuilA-FML developed the strongest DTH and QS21-FML animals showed the highest serum IFN-gamma concentrations. The reduction of parasitic load in the liver in response to each FML-vaccine formulation was: 52% (P < 0.025) for BCG-FML, 73% (P < 0.005) for R-FML, 93% (P < 0.005) for QuilA-FML and 79.2% (P < 0.025) for QS21-FML treated animals, respectively. Protection was specific for R-FML and QS21-FML while the QuilA saponin treatment itself induced 69% of LDU reduction. The FML-saponin vaccines promote significant, specific and strong protective effects against murine visceral leishmaniasis. BCG-FML induced minor and non-specific protection while IL 12-FML, although enhancing the specific antibody and IDR response, failed to reduce the parasitic load of infected animals. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: murine visceral leishmaniasis; adjuvants; saponin; QuilA; QS21; IL12